Childhood visual impairment in England: a rising trend. Issue 5 (6th December 2012) - Mitry, Danny; Bunce, Catey; Wormald, Richard; Bowman, Richard
Abstract : Aim: To explore temporal trends in the incidence of childhood blindness and partial-sight registration in England between 1982 and 2011. Methods: We obtained blind and partial-sight registration data for all new individuals registered annually in England. We calculated the age-specific incidence of new registrations for childhood blind and partial sight. Results: The incidence of new registration for blindness of all ages has decreased from 2.6 per 10 000 in 1982 to 1.7 per 10 000 in 2011, however the annual incidence of new paediatric blind registration has increased, with an incidence of 0.17 per 10 000 in 1982, doubling to 0.41 per 10 000 in 2011. The annual incidence of new paediatric partial-sight registration showed a comparable trend. Conclusions: Over 30 years, there has been a greater than twofold increase in blind and partial-sight registration in children in England. Better awareness of this is needed to ensure adequate resources are available to help these children.